Perioperative nursing of patients with verrucous epidermal nevi (疣状表皮痣手术患者围手术期护理体会) - SI Tao (司桃); FAN Xiaoli (范晓莉); LI Huixian (李慧娴); PEI Pei (裴培); DING Eryan (丁二艳) (Association of Integrative Nursing, 2023)
This paper summarized the nursing management for 33 patients with verrucous epidermal nevi. Psychological guidance and health education were carried out before surgery. Nurses had enhanced the intraoperative coordination and monitoring of illness condition. Key issues of postoperative nursing included wound care, body position care, perineal care; nutrition support, medical care and health education before discharge form hospital. The comprehensive perioperative nursing interventions could effectively improve the wound healing, reduce the risk of complications and improve patients' quality of life. (本文总结33例疣状表皮痣手术患者的围手术期护理经验。术前做好心理辅导和健康教育, 完善术前准备; 术中密切配合、积极观察患者生命体征; 术后开展创面护理、体位护理、会阴部护理、饮食护理、用药护理等全面护理; 出院前给予健康指导。护士通过实施精细的围术期护理, 能有效促进创面愈合, 降低并发症风险, 提高患者生活质量。)